Charge identification of fragments produced in 16O beam interactions at 200 MeV/n and 400 MeV/n on C and C2H4 targets - Galati, G.; Boccia, V.; Alexandrov, A.; Alpat, B.; Ambrosi, G.; Argirò, S.; Barbanera, M.; Bartosik, N.; Battistoni, G.; Bisogni, M. G.; Bruni, G.; Cavanna, F.; et al. (Frontiers in Physics, 2024)
Introduction: Charged Particle Therapy plays a key role in the treatment of deep-seated tumours, because of the advantageous energy deposition culminating in the Bragg peak. However, knowledge of the dose delivered in the entrance channel is limited by the lack of data on the beam and fragmentation of the target. Methods: The FOOT experiment has been designed to measure the cross sections of the nuclear fragmentation of projectile and target with two different detectors: an electronic setup for the identification of Z ≥ 3 fragments and a nuclear emulsion spectrometer for Z ≤ 3 fragments. In this paper, we analyze the data taken by exposing four nuclear emulsion spectrometers, with C and C2H4 targets, to 200 MeV/n and 400 MeV/n oxygen beams at GSI Helmholtzzentrum für Schwerionenforschung (Darmstadt, Germany), and we report the charge identification of produced fragments based on the controlled fading induced on nuclear emulsion films. Results: The goal of identifying fragments as heavy as lithium has been achieved. Discussion: The results will contribute to a better understanding of the nuclear fragmentation process in charged particle therapy and have implications for refining treatment planning in the presence of deep-seated tumors.